2012
DOI: 10.1128/mcb.00513-12
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Functional Analysis of JMJD5 Indicate an Alternate Specificity and Function

Abstract: JMJD5 is a Jumonji C (JmjC) protein that has been implicated in breast cancer tumorigenesis, circadian rhythm regulation, embryological development, and osteoclastogenesis. Recently, JMJD5 (also called KDM8) has been reported to demethylate dimethylated Lys-36 in histone H3 (H3K36me2), regulating genes that control cell cycle progression. Here, we report high-resolution crystal structures of the human JMJD5 catalytic domain in complex with the substrate 2-oxoglutarate (2-OG) and the inhibitor N-oxalylglycine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 53 publications
7
68
0
Order By: Relevance
“…These results suggest that both the association of JMJD5 with HBx and the hydroxylase activity in JMJD5 are required for efficient replication of HBV. JMJD6, which has a JmjC domain structurally similar to that of JMJD5 (36,38), possesses lysyl-hydroxylase activity and catalyzes the U2 small nuclear ribonucleoprotein auxiliary factor 65-kDa subunit (U2AF65) to regulate RNA splicing (75) and hydroxylation of lysine residues in histone (76,77). Further studies are needed to identify the molecular targets of JMJD5 in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that both the association of JMJD5 with HBx and the hydroxylase activity in JMJD5 are required for efficient replication of HBV. JMJD6, which has a JmjC domain structurally similar to that of JMJD5 (36,38), possesses lysyl-hydroxylase activity and catalyzes the U2 small nuclear ribonucleoprotein auxiliary factor 65-kDa subunit (U2AF65) to regulate RNA splicing (75) and hydroxylation of lysine residues in histone (76,77). Further studies are needed to identify the molecular targets of JMJD5 in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analyses have shown that JMJD5 exhibits hydroxylase activity rather than demethylase activity (36,37). The structure of the jumonji C domain of JMJD5 was conserved with the C-terminal transactivation domains of the factor inhibiting hypoxia-inducible 1 alpha (FIH-1) and JMJD6 (36,38). The C-terminal transactivation domain of FIH-1 exhibits an asparaginyl hydroxylase activity to catalyze hydroxylation of Asp 803 of hypoxia-inducible factor (39).…”
Section: H Epatitis B Virus (Hbv) Is An Enveloped Virus Belonging To Thementioning
confidence: 99%
“…The exact functions of JMJD5 remain controversial. JMJD5 has been suggested to possess H3K36 lysine demethylase (21) and/or a hydroxylase activities (22,23). The possibility remains that JMJD5 and some other "orphan" JmjC proteins target methyl arginines in histones and/or other proteins via different mechanisms.…”
Section: Significancementioning
confidence: 99%
“…JMJD5 was reported to be histone H3K36me2 demethylase and non-histone protein hydroxylase (13,16). The crystal structure of JMJD5 showed that, in the catalytic site, Fe 2ϩ could be chelated by residues His 321 , Asp 323 , and His 400 (27,28). This HX(D/E)X n H motif is highly conserved in JmjC domain-containing proteins and is important for their catalytic activity (29).…”
Section: Depletion Of Jmjd5 Leads To Accumulation Of Mitotic Cells Anmentioning
confidence: 99%